2022
DOI: 10.3390/ijms231710057
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Patterns of the SWEET Gene Family in Bletilla striata and its Responses to Low Temperature and Oxidative Stress

Abstract: SWEETs (sugars will eventually be exported transporters), a well-known class of sugar transporters, are involved in plant growth and development, sugar transport, biotic and abiotic stresses, etc. However, to date, there have been few investigations of SWEETs in Orchidaceae. In this study, 23 SWEET genes were identified in Bletilla striata for the first time, with an MtN3/saliva conserved domain, and were divided into four subgroups by phylogenetic tree. The same subfamily members had similar gene structures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Species with more collinear gene pairs (V. planifolia and B. striata) appeared to have relatively closer evolutionary relationships. This was consistent with the collinearity results of other B. striata gene families [42].…”
Section: Discussionsupporting
confidence: 92%
“…Species with more collinear gene pairs (V. planifolia and B. striata) appeared to have relatively closer evolutionary relationships. This was consistent with the collinearity results of other B. striata gene families [42].…”
Section: Discussionsupporting
confidence: 92%
“…SWEET proteins are mainly localized on the plasma and the tonoplast, while, a few members are also localized on the endoplasmic reticulum and the Golgi membranes ( Chen L. Q. et al., 2015 ; Jeena et al., 2019 ; Breia et al., 2021 ). AtSWEET13 ( Kanno et al., 2016 ) in Arabidopsis , PbSWEET4 ( Ni et al., 2020 ) and PuSWEET15 ( Li et al., 2020 ) in pear, BsSWEET15 and BsSWEET16 ( Lu et al., 2022 ) in Bletilla striata , and SlSWEET14 ( Zhang et al., 2021 ) in tomato, are also localized on the plasma membrane. The localization of sugar transporter ClVST1 shifted from tonoplast in wild-type watermelon to plasma membrane in sweet watermelon, which increased sugar sink potency ( Ren et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous members of the SWEET gene family in higher plants, and studies on the SWEET gene family have been reported: There are 17, 21, 24, 29, 34, 27, 17, 27, 16, 22, 20, 19, 23, 25, and 25 SWEETs identified in Arabidopsis thaliana [10], rice [16], maize [17], tomato [18], Brassica rapa [19], garlic [20], grapes [21], apples [22], litchi [23], watermelon [24], longan [25], jujube [7], Bletilla striata [26], Dendrobium officinale [27], and rose [28], respectively. The members of the SWEET gene family have the specificity of space-time and tissue expression, and there are obvious differences in the types of transported sugar [29].…”
Section: Introductionmentioning
confidence: 99%